The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1756-185x.13571
|View full text |Cite
|
Sign up to set email alerts
|

Association between use of Chinese herbal medicine and depression risk in patients with rheumatoid arthritis: A nationwide retrospective cohort study

Abstract: Aim: Depression is a common mental disorder in rheumatoid arthritis (RA) patients and may provoke the onset of poor clinical prognoses. In view of this, whether or not the use of Chinese herbal medicines (CHMs) can alleviate the risk of depression still remains unclear. We conducted a longitudinal cohort study to evaluate the association between CHMs us and depression risk among RA patients. Method:Using claims data from the National Health Insurance of Taiwan, we identified 6609 newly diagnosed RA patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Second, we added to the analysis prescription of biological agents, taken for six months or longer, which is a common surrogate used for RA severity in the administrative claims data. 11,38 These sensitivity analyses revealed that disease severity was not likely to alter the veracity of our findings that adding CHMs to conventional therapy reduced the risk of fracture in RA patients. Fourth, due to the use of a cohort study design, rather than a randomized controlled trial, inferences regarding the beneficial effect of CHMs on reducing fracture risk are likely limited due to unmeasured or unknown confounders.…”
Section: Chms Name Ingredients or Generic Namementioning
confidence: 64%
See 2 more Smart Citations
“…Second, we added to the analysis prescription of biological agents, taken for six months or longer, which is a common surrogate used for RA severity in the administrative claims data. 11,38 These sensitivity analyses revealed that disease severity was not likely to alter the veracity of our findings that adding CHMs to conventional therapy reduced the risk of fracture in RA patients. Fourth, due to the use of a cohort study design, rather than a randomized controlled trial, inferences regarding the beneficial effect of CHMs on reducing fracture risk are likely limited due to unmeasured or unknown confounders.…”
Section: Chms Name Ingredients or Generic Namementioning
confidence: 64%
“…Despite the interest in CHMs, only a few studies have reported the characteristics of CHMs usage patterns in RA patients. 9 , 11 To the best of our knowledge, no previous studies have directly determined an association between CHMs use and osteo-protective influence among RA patients. This study, therefore, aimed to corroborate the association, over time, between CHMs use and incident osteoporotic fracture among RA patients, using a nationwide medical claims database representative of the Taiwanese population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, therefore, used the frequency of visits to Chinese medicine physicians to verify the CHMs exposure of each insomniac patient. Those receiving CHMs to treat insomnia for more than 30 days were deemed CHMs users, whereas those treated for 30 days or less were considered non-CHMs users (12,13). Based on this procedure, 31,238 cases were designated as CHMs users.…”
Section: Study Participantsmentioning
confidence: 99%
“…The mechanism of Jia-Wei-Xiao-Yao-San (JWXYS) in autoimmune disease was observed to increase synaptic plasticity and decrease the levels of inflammatory markers by upregulating the expression of hippocampal brain-derived neurotrophic factor (BDNF) (5)(6)(7). Suan-Zao-Ren-Tang (SZRT) could regulate the gammaaminobutyric acid-ergic(GABA) system in plasma which is crucial in the etiology of psychiatric disorders (8). The results of studies conducted on animals have indicated that Gan-Lu-Yin (GLY) can influence vascular smooth muscle activity (9) and exert anti-inflammatory effect (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%